Countering the negative impacts of deepfake technology: Approaches for effective combat - Ghediri, Karima (International journal of economic perspectives, 2024)
The rapid rise of deepfake technology poses significant challenges at individual, societal, and national levels. Although there are positive applications, malicious uses have largely overshadowed them, making it crucial to examine available methods for addressing this growing threat. This paper reviews three primary approaches to mitigate the risks of deepfake technology: technical detection methods, legal and regulatory frameworks, and media literacy initiatives. While no single solution fully addresses the challenges of deepfake misuse, a comprehensive understanding of these combined strategies can provide a strong foundation for reducing the harmful impacts of this technology.